Intermittent Dieting: Theoretical Considerations for the Athlete - Jackson James Peos; Layne Eiseman Norton; Eric Russell Helms; Andrew Jacob Galpin; Paul Fournier (MDPI AG, 2019)
Athletes utilise numerous strategies to reduce body weight or body fat prior to competition. The traditional approach requires continuous energy restriction (CER) for the entire weight loss phase (typically days to weeks). However, there is some suggestion that intermittent energy restriction (IER), which involves alternating periods of energy restriction with periods of greater energy intake (referred to as ‘refeeds’ or ‘diet breaks’) may result in superior weight loss outcomes than CER. This may be due to refeed periods causing transitory restoration of energy balance. Some studies indicate that intermittent periods of energy balance during energy restriction attenuate some of the adaptive responses that resist the continuation of weight and fat loss. While IER—like CER—is known to effectively reduce body fat in non-athletes, evidence for effectiveness of IER in athletic populations is lacking. This review provides theoretical considerations for successful body composition adjustment using IER, with discussion of how the limited existing evidence can be cautiously applied in athlete practice.